Evolution of hepatic encephalopathy over time: ecological data from a tertiary referral centre for hepatology. Issue 1 (January 2023) - Mangini, C.; Zarantonello, L.; Formentin, C.; Giusti, G.; Angeli, P.; Montagnese, S.
Abstract: Objectives: Few data on hepatic encephalopathy (HE) over time are available, thus our aim was to study its evolution in patients with varying degree of HE on first assessment. Methods: Eighty-six patients with cirrhosis (age = 58 ± 11 years; males = 72) were evaluated 2–10 times for liver transplantation selection purposes, differential diagnosis or treatment optimization. The presence/severity of HE was assessed by clinical and neuropsychiatric indices [ Psychometric Hepatic Encephalopathy Score (PHES) and electroencephalography (EEG)] and the severity of liver disease by the Model for End-Stage Liver Disease (MELD) score. Treatment was instituted/modified after each evaluation. Results: Amongst 23 unimpaired patients, 56/6% remained unimpaired, 35/3% developed covert HE, 9/0% developed overt HE on second/third evaluation. Amongst 32 patients with covert HE, 25/10% became unimpaired, 44/19% remained covert, 31/13% developed overt HE. Finally, amongst 32 patients with overt HE, 19/16% became unimpaired, 25/13 % became covert and 56/25% remained overt. PHES results improved in patients with overt HE and EEG worsened over time (despite remaining normal) in unimpaired patients. In patients with multiple evaluations, HE evolution was manifold and difficult to predict. Conclusions: HE evolution over time is variable and largely dependent on HE history/management. These data support the concept that HE is an essentially reversible condition.